DEFORESTASI SEBAGAI DAMPAK MODERNISASI DI TAMIANG : STUDI EKOTEOLOGIS - Fitriani, Fitriani; Harahap, Syahrin; Harahap, Elly Warnisyah; Lubis, Dahlia; Siregar, Husna Sari (UIN Sumatera Utara Medan, 2026)
Deforestation in Aceh Tamiang Regency has become a serious environmental issue driven by the expansion of oil palm plantations, infrastructure development, and industrial activities fueled by waves of modernization. The loss of primary and secondary forest cover has not only caused soil erosion, recurrent flooding, and a decline in biodiversity, but has also triggered land conflicts and deepened poverty among indigenous communities dependent on the forest. This study aims to analyze the relationship between modernization and deforestation in Tamiang, examine the phenomenon through an ecotheological approach, and formulate the contribution of Islamic theological values to environmental conservation efforts. The research employs a qualitative-descriptive method with ecotheological and sociological approaches, relying primarily on literature review techniques (Qur’an, academic journals, and recent news sources). The main theoretical framework is Islamic ecotheology, grounded in the principles of khalifah (vicegerent of God on earth), amanah (trust/responsibility), mizan (balance), and rahmatan lil ‘alamin (mercy to all creation). Key findings reveal that modernization has accelerated deforestation through an economic logic that prioritizes short-term profit, while the ecotheological perspective exposes deforestation as a moral and spiritual crisis resulting from humanity’s deviation from its role as khalifah. Theoretically, this study enriches contextual ecotheology scholarship in Indonesia; practically, it offers religion-based environmental ethics recommendations for local communities and policy inputs for integrating theological values into sustainable forest management in religiously rooted regions.